Recubrimiento comestible de almidón de yuca y lactobacillus acidophilus microencapsulado para la conservación de papaya troceada de lV gama - López Zambrano, César Fabián (2019)
The objective of the present investigation was to evaluate the useful life period of the papaya cut by the use of edible coating of cassava starch, with the addition of microencapsulated L. acidophilus. A completely randomized block design was applied in a bifactorial arrangement A * B + 1 with three replications for each treatment, taking as an experimental unit 250 g of cut papaya. For this, the following factors were manipulated: Concentration of cassava starch (0.5, 1.0, 1.5% w / v) and b: Concentration of L. acidophilus (10 5 and 10 8 CFU/g) obtaining as a result 6 treatments plus a control (without treatment). The samples were stored at 8 ° C and 90% RH for 12 days. Physical variables (firmness, cohesiveness, weight loss, soluble solids, titratable acidity) and microbiological variables (aerobic mesophils, molds and yeast) were evaluated every 4 days. The physical characteristics were analyzed with parametric statistics, the interaction of the factors had significance in titratable acidity, the other physical variables had significance separately; For the microbiological variables linear regression was applied, all the treatments had better behavior in relation to the control, 0.5% of cassava starch maintained the physical and chemical characteristics, while 1.5% with 108 of L. acidophilus was the one had a longer shelf life compared to all treatments. It is concluded that the cassava starch maintains the physical and chemical characteristics, while the interaction of the two factors extends the shelf life in 15 days of the cut papaya.